2021
DOI: 10.4103/jehp.jehp_956_20
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of social support, social capital, and coping on the positive state of mind of Iranian older people with human immunodeficiency virus/acquired immunodeficiency syndrome

Abstract: BACKGROUND: Social resources help to adapt to stress and might positively affect the well-being of individuals with severe conditions like human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). The present study investigates the effect of social support, social capital, and coping in a positive state of mind of Iranian older people with HIV/AIDS. MATERIALS AND METHODS: This cross-sectional study was conducted on 160 older people with HIV referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Only six studies (Brown et al, 2023; Emlet et al, 2017; Hampton et al, 2013; Nguyen et al, 2018; Porter et al, 2017, 2019) reported having Hispanic/Latino participants among their sample (range 4–34%). Five studies did not report data on race/ethnicity (Drewes et al, 2021; Fumaz et al, 2015; Huang et al, 2018; Liu et al, 2014; SoleimanvandiAzar et al, 2021) possibly due to the sample largely being homogenous. One study acknowledged ethnic differences within the sample, but the exact differences were unclear (Xu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only six studies (Brown et al, 2023; Emlet et al, 2017; Hampton et al, 2013; Nguyen et al, 2018; Porter et al, 2017, 2019) reported having Hispanic/Latino participants among their sample (range 4–34%). Five studies did not report data on race/ethnicity (Drewes et al, 2021; Fumaz et al, 2015; Huang et al, 2018; Liu et al, 2014; SoleimanvandiAzar et al, 2021) possibly due to the sample largely being homogenous. One study acknowledged ethnic differences within the sample, but the exact differences were unclear (Xu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…SoleimanvandiAzar et al (2021) investigated coping and positive state of mind among 160 Iranian older PWH ages 50 years and older (mean age 65.82 years, SD = 6.69). Bivariate correlation analysis showed that coping had a significant positive relationship with positive state of mind ( r = .33, p < .001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of social capital in a community is recognized as one of the most influential on an individual’s health [12, 13]. An example of social capital is a collection of informal standards or values that are held in common by members of a group with whom collaboration is possible.…”
Section: Introductionmentioning
confidence: 99%